Problematyka zaskarżania uchwał rad nadzorczych spółek kapitałowych - Mizerski, Dominik (Wydawnictwo Naukowe UAM, 2020)
Artykuł przedstawia kwestie związane z problematyką charakteru prawnego uchwał rad nadzorczych spółek kapitałowych oraz podstawą ich zaskarżania. W artykule zaprezentowano zmienność stanowisk orzecznictwa oraz doktryny na przedstawioną problematykę. Ewaluowały one począwszy od braku możliwości zaskarżania uchwał rad nadzorczych spółek kapitałowych, poprzez ich zaskarżanie w drodze analogicznego stosowania przepisów o zaskarżaniu zgromadzeń spółek kapitałowych, aż do ostatecznego zaakceptowania dopuszczalności ich zaskarżania w drodze powództwa o ustalenie. W opracowaniu wskazano również na korzyści oraz zagrożenia związane z przyjęciem jednego z przedstawionych stanowisk.

The article presents issues connected with the problem of legal character of resolutions of supervisory board in capital companies and the basis for filing an appeal against them. The paper refers to the variability of doctrine and jurisprudence views on the presented issue. The views evolved from the inability to file an appeal against resolutions of supervisory boards in companies, through the admissibility of the appeal by applying relevant provisions concerning resolutions of general meetings in companies, up to the standpoint regarding the possibility of appealing against them by bringing an action for establishment. The article indicates also benefits and risks of adopting one of the presented positions.
Filing an appeal against resolutions of supervisory boards in companies
Keywords: uchwały rad nadzorczych; resolutions of supervisory boards; zaskarżanie uchwał; appealing against resolutions; spółki kapitałowe; capital companies